Physicochemical and Sensory Properties of Plant-Based Milk Alternative Produced from Pigeon Pea and Soybean - Azra, Jeallyza Muthia; Nurdiani, Reisi; Nasution, Zuraidah; Aries, Muhammad; Sutiari, Ni Ketut (Jurnal Teknologi dan Industri Pangan, 2025)
The popularity of plant-based milk alternatives (PBMA) has been growing due to environmental concerns and health benefits. This study aimed to develop and evaluate a novel PBMA formulation combining pigeon pea and soybean at three different ratios (40:60, 50:50, and 60:40), focusing on their physicochemical characteristics, sensory properties, and antioxidant activity. In this study, significant differences (p<0.05) were found in the physicochemical properties of the samples, while sensory acceptability showed no significant differences (p>0.05). Increasing the proportion of pigeon pea resulted in a lower level of ash, protein, fat, color, viscosity, and pH, while the content of moisture, carbohydrate, and soluble solids increased. The formulations contained 91.84‒92.39% moisture; 0.09‒0.12% ash; 0.80‒1.48% protein; 0.81‒1.04% crude fat; and 5.52‒5.91% carbohydrate. Additionally, they had lightness values of 59.74‒68.57; greenness/redness values of -0.53‒0.68; yellowness values of 6.60‒8.13; viscosities of 11.42‒12.50 cP; soluble solids of 6.00‒9.00 °Brix; and pH of 6.69‒6.72. The sensory evaluation ranged from “neither like nor dislike” to “slightly like” (5.24–5.97 on a 9-point scale), indicating moderate acceptability across all formulations. Despite being acknowledged as having a beany aroma, the panelists identified sweet and creamy notes with low bitterness in the sample, contributing to a relatively pleasant flavor. Furthermore, the 50:50 pigeon pea-to-soybean formulation contained daidzein as the predominant isoflavone and demonstrated high antioxidant activity (91.90% DPPH inhibition). These findings suggest that the developed PBMA is a promising functional beverage with good nutritional and sensory qualities.